Culture-and nonculture-based antibiotics for complicated soft tissue infections are comparable - Ronald Irwanto; Suhendro Suhendro; Khie Chen; Murdani Abdullah (Universa Medicina, 2013)
BACKGROUNDData collected in 2010 from Cipto Mangunkusumo Hospital indicate thatcomplicated skin and soft tissue infections accounted for more than 10% ofcases. Etiological diagnoses are based on the findings on bacterial culture andthus evaluation of the effectiveness of bacterial culture becomes a necessity.The purpose of this study was to evaluate the operational effectiveness ofbacterial culture for etiological diagnosis of complicated skin and soft tissueinfections.METHODSThis was a historical cohort study using secondary data of patients withcomplicated skin and soft tissue infections admitted for hospitalization to CiptoMangunkusumo Hospital, Jakarta from July 2011 to July 2012. The 90 subjectsmeeting the inclusion and exclusion criteria were divided into 2 groups of 45patients each. Group 1 comprised patients who received initial antibiotic therapyaccording to cultural results, while the patients in group 2 received initial antibiotictherapy without reference to cultural results. Successful diagnostic culture wasassessed by the absence of therapeutic failure. Therapeutic failure wasdetermined using 3 parameters that had to be fulfilled, viz. absence of antibioticescalation, repeat operations, and clinical deterioration. The latter parameterwas assessed by clinical judgement of the attending physician.RESULTSAfter controlling for confounding variables (age, severity of infection,comorbidity), there was no statistical difference in therapeutic success betweenculture-based and non-culture based initial antibiotic therapies (OR=0.45,p=0.085).CONCLUSIONThis study demonstrates the ineffectiveness of bacterial culture as a diagnosticcriterion for appropriate antibiotic therapy of complicated skin and soft tissueinfections.